(untitled) (Panacea Journal of Medical Sciences, 2020)
Background: Hepatitis B and C are globally emerging health problems. Being Hepatitis B and C are parenterally transmitted viruses both resulting in liver cirrhosis and hepatocellular carcinoma. Both accounting for the substantial proportion of hepatic diseases worldwide. Although both are hepatotropic viruses both are sharing common modes of transmission and mostly affect the young population. Prevalence of Hepatitis B in India is 3.7% and Hepatitis C is 1%. Hepatitis B is the second most common cause of acute viral hepatitis in India. Chance of transmission of Hepatitis B by needle stick injury is 30% and of Hepatitis C is 3%. Intravenous drug abusers were found to be most common mode of transmission of Hepatitis C. Aims: As both Hepatits B, and C are parenterally transmitted infections and land up into chronicity. To prevent their complications the present study was done to screen out these cases at the very early stage with the test with high sensitivity and specificity. Materials and Methods: The presence of HBsAg and anti HCV antibodies were studied serologically in patients blood by Electro -chemiluminescence immune-assay method. Results: The seroreactivity of positive cases were observed. Conclusion: Henceforth seroreactivity of both the viruses studied among different age groups in both the sexes to initiate the treatment at right time to prevent its long term complications such as chronicity and for good prognosis by highly sensitive and specific test.